Long-term Impacts of Tourism Student Exchange Program - Priyanto, Yumnaa Adina Ulfah; Andrianto , Tomy (Politeknik Negeri Bandung, 2022)
The student exchange program certainly provides added value and benefits that contribute to sustainable tourism development as part of educational tourism. Purpose of this study to identify the long-term impact of tourism student exchange programs in ASEAN. Student exchanges allow students to gain in-depth insight into global perspectives and cross-cultural understanding, especially related to tourism studies. This study uses a qualitative method by interviewing seven informants enrolled in the program from 2018 to 2019 to Thailand and Malaysia. Descriptive analysis of the first code cycle is used to analyse and answer the research objectives. As a result, students sense long-term changes from the program, such as improving communication in foreign languages, self-confidence, sense of independence, responsibility in decision-making or participant actions, priorities for the future, and intercultural understanding.